Safety of potassium-bearing citrate in patients with renal transplantation: A case report. Issue 42 (October 2017) - Wang, Lin; Cui, Yinglin; Zhang, Jianwei; Zhang, Qinsheng
Abstract: Rationale: Urinary lithiasis is one of severe postoperative complications in patients undergoing renal transplantation, possibly leading to anuria, urinary infection, or even acute renal failure. Potassium sodium hydrogen citrate (PSHC), a potassium-bearing citrate, is commonly prescribed to prevent stone formation. Patient concerns: A 25-year-old man (patient 1) and a 31-year-old man (patient 2) receiving renal transplantation for end-stage renal disease (ESRD) were enrolled in this study. They were given 10 g/day of PSHC granules from the ninth day to the 17th day after surgery. Patient 1 presented chest tightness, nausea, muscle weakness, and ascending paralysis on the 10th day. Patient 2 presented weak waves on EGG on the 17th day. Moreover, their serum potassium concentrations (SPCs) were 7.67 and 6.05 mmol/L, respectively. Diagnosis: Acute hyperkalemia. Interventions: Hemo-filtration was performed for patient 1, while patient 2 received 10% calcium gluconate 10 mL, 5% NaHCO3 125 mL, and 10% glucose 500 mL with the addition of 10 units of insulin through intravenous drip. Outcomes: Their SPCs dropped to the normal range. Lessons: Physicians should pay close attentions to potential risks caused by PSHC, and monitor the SPCs to minimize the occurrence of hyperkalemia.